Pericardial effusion among children: Retrospective analysis of the etiology and short‐term outcome in a referral center in the south of Iran. Issue 3 (23rd May 2022) - Mehdizadegan, Nima; Mohammadi, Hamid; Amoozgar, Hamid; Pournajaf, Samira; Edraki, Mohammad Reza; Naghshzan, Amir; Yazdani, Mohammad Nima
Abstract: Background and Aims: We reinvestigated the causes, symptoms, and management of childhood pericardial effusion (PE) and its gradual changes during recent years in a referral pediatric cardiology center in the south of Iran. Methods: We retrospectively analyzed the profile of PE patients who were under 18 years old from 2015 to 2020. The patient's demographic, clinical, and paraclinical information was extracted and analyzed using SPSS software. Result: In general, 150 out of 63, 736 admitted patients (0.23% of the total pediatric admissions) were diagnosed with PE (male/female 1:1.17). The median age was 3.25 years (range: 2 days to 18 years; interquartile range: 9.5), and 50% of them were under 3 years of age. 32.6% had moderate to severe PE. Most patients presented with acute symptoms (68%) and respiratory problems, as the most common symptoms (30.6%). Tamponade signs were presented in 2% ( n = 3) of the patients, and 80.7% ( n = 121) were in a stable hemodynamic condition. In total, renal failure (22%) and parapneumonic effusion were the leading etiologies. Viral (7%) and bacterial (5%) pericarditis were the seventh and eighth causes; however, in severe cases, renal failure (22%) and bacterial pericarditis (14%) were dominant. In total, 14.1% ( n = 21) of the patients needed pericardiocentesis that increased to 78.3% ( n = 18) in severe cases. Only 6% had persistent PE for more than 3 months. Conclusion: Childhood PE is mostly a result of renal failure and noninfectious causes. True pericarditis cases are not common, except in severe cases. It is more common in less than 3‐year‐old patients, and chronicity is rare. Severe cases had a high chance of pericardiocentesis, but other cases were mainly managed by treatment of the underlying causes.